Marcadores inflamatórios e fatores neurotróficos na migrânea - Halina Duarte (2014)
Introduction: Migraine physiopathology is still largely unknown. Inflammatory mediators and neurotrophic factors have been studied in the context of migraine, however, their role is not yet well established. Objectives: The aim of the present study was to evaluate the serum levels of several inflammatory markers and neurotrophic factors, and their association with clinical parameters and psychiatric comorbidities in patients with migraine compared with controls. Methods: This cross-sectional study was conducted on a sample of 50 patients with migraine and 50 healthy controls, matched by age and gender. Patients and controls were submitted to: Beck depression and anxiety inventories, headache impact test (HIT-6), and allodynia symptom checklist. Adiponectin, chemokines (CCL2/MCP-1, CCL3/MIP-1, CCL5/RANTES, CCL11/Eotaxin, CCL24/Eotaxin 2, CXCL8/IL-8 and CXCL10/IP-10) and neurotrophic factors (BDNF, GDNF, NGF, NT-3 and NT-4/5) serum levels were measured by ELISA. Results: The serum levels of adiponectin, CXCL8/IL-8 and CCL3/MIP-1 were significantly higher among patients with migraine when compared with controls, even after controlling for anxiety and depression scores. Migraine patients and controls did not differ in their levels of neurotrophic factors. No significant differences were found in levels of inflammatory markers and neurotrophic factors in episodic and chronic migraine, as well as according to the presence or absence of aura. Levels of inflammatory markers and neurotrophic factors did not correlate with frequency of attacks, impact of migraine, as well as the score of allodynia. Conclusion: Our results reinforce the idea that inflammatory mechanisms are involved in the pathophysiology of migraine, as demonstrated by increased serum levels of adiponectin and chemokines CXCL8/IL-8 and CCL3/MIP-1 in patients with migraine during the interictal period, regardless of the presence of symptoms of anxiety and depression.